Intermetallics evolution and shear strength of carbon nanotubes- reinforced sn-5sb solder on copper board - Dele-Afolabi, Temitope Theophilus (2015)
Critical evaluation of interconnection materials developed from composite solder materials and a comprehensive comparison of the joints with the host solder alloy are cardinal to the quest of divulging a more decent and dependable alternative to the existing solder candidate. In this study, the effects of multi-walled carbon nanotubes (MWCNTs) addition on the physical properties, intermetallic compound formation and shear strength property were explored. Plain Sn-5Sb solder system and carbon nanotubes reinforced solder systems (Sn-5Sb-xCNT;x=0.01, 0.05 & 0.1wt.%) were developed through the powder metallurgy route. In order to characterize the solder joint microstructure and intermetallic compound growth in the samples, plain and composite solders were reflowed on the copper (Cu) substrate at a peak temperature of 270°C. Similarly, the single-lap solder joint system was fabricated and used to evaluate the shear strength of all solder samples using the same reflow temperature as in the case of the solder/Cu joint. After the reflow process, isothermal aging study was conducted on the solder/Cu joints and the single-lap solder joint system at 170°C for time intervals of 500h, 1000h and 1500h. The melting temperature results indicated that the presence of carbon nanotubes addition to the solder matrix lead to a marginal decrease in the peak temperature of the composite solders due to high surface free energy of MWCNTs in the solder matrix with the 0.1wt.% CNTs solder reinforcement having a maximum drop of 2.72°C in melting temperature as compared to the plain solder counterpart. More so, it was evident from the study that the wetting angle decreased with increasing CNTs addition. The Sn-5Sb-0.05CNT solder joint exhibited a 14% reduction in the wetting angle result than that of the plain solder joint whereas, increasing the CNTs content up to 0.1wt.% resulted in a marginal leap of the wetting angle. Microstructural analysis of all samples using the combined study of the SEM and EDX analysis confirms the formation of a dark dendritic shaped Cu6Sn5 intermetallic compound (IMC) phase floating in the solder bump which coarsens as aging time increased. Besides, light grey precipitates were spotted within the β-Sn matrix. A sparse dispersion of the precipitates was observed in the composite solder joints as against the plain solder joints for all subjected conditions. From the IMC thickness data retrieved, a minimal retardation in the total intermetallic compound layer growth was observed in the composite solder joints with respect to the plain solder joint for the reflow samples, where IMC thicknesses of 2.60μm and 3.04μm were recorded for the Sn-5Sb-0.05CNT and Sn-5Sb solder joints respectively. Meanwhile, IMC layer growth in the aged samples was observed to have being remarkably suppressed with the Sn-5Sb-0.05CNT solder joint having a value of 11.99μm for 1500h aging condition which indicates 2.64μm reduction in the value of the plain solder joint counterpart as well as the inhibiting role played by the CNTs in prohibiting the diffusion of Sn atoms needed for the interfacial IMC layer growth. Similarly, owing to the excellent mechanical properties and the level of IMC layer retardation shown by the composite solder joints, the 0.01wt.% CNTs solder reinforcement gave the highest shear strength than every other single-lap solder joints across board.